2011
DOI: 10.1007/s10865-011-9343-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the connection between spiritual well-being and physical health: an examination of ambulatory blood pressure, inflammation, blood lipids and fasting glucose

Abstract: Growing research has demonstrated a link between spiritual well-being and better health; however, little is known about possible physiological mechanisms. In a sample of highly religious healthy male and female adults (n = 100) ages 19-59 (m = 28.28) we examined the influence of spiritual well-being, as measured by the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT-Sp-Ex), on physiological risk factors for heart disease. Specifically we examined 24-h ambulatory blood pressure (BP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 79 publications
1
23
1
4
Order By: Relevance
“…Inconsistent with the present study, a study of 100 married, primarily non-Hispanic White adults, found that higher levels of Spiritual Well-being (i.e. total scores on the FACIT-Sp-Ex) were significantly associated with lower fasting glucose and marginally lower triglycerides (Holt-Lunstad et al, 2011). However, that study also found non-significant associations between Spiritual Well-being, HDL and LDL cholesterol, consistent with the present study’s null findings regarding HDL cholesterol.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Inconsistent with the present study, a study of 100 married, primarily non-Hispanic White adults, found that higher levels of Spiritual Well-being (i.e. total scores on the FACIT-Sp-Ex) were significantly associated with lower fasting glucose and marginally lower triglycerides (Holt-Lunstad et al, 2011). However, that study also found non-significant associations between Spiritual Well-being, HDL and LDL cholesterol, consistent with the present study’s null findings regarding HDL cholesterol.…”
Section: Discussioncontrasting
confidence: 91%
“…Multidimensional aspects of R/S, such as religious well-being, existential well-being, composite spiritual well-being, and forgiveness, in addition to frequency of prayer and service attendance have been associated with more favorable levels of cardiovascular and cardiometabolic risk factors. These include lower physiological reactivity in response to stress (Edmondson et al, 2005; Tartaro et al, 2005), lower ambulatory blood pressure, and lower levels of inflammatory markers, fasting glucose, cholesterol, and triglycerides (Doster et al, 2002; Holt-Lundstad et al, 2011). …”
mentioning
confidence: 99%
“…Of those, four (50%) reported significant inverse relationships [137][138][139] or a reduction in CRP in response to a R/S intervention [140]; the other four studies found no association. More recent research supports an inverse relationship between R/S and CRP [141].…”
Section: Cardiovascular Functions and Inflammatory Markersmentioning
confidence: 87%
“…Spiritual wellbeing may be cardio protective, as it has been significantly related to lower systolic and diastolic BP, hs-C-reactive protein, fasting glucose, and marginally lower triglycerides [54].…”
Section: Cardio-vascular Diseasesmentioning
confidence: 99%